'Hot cross bun' sign in a case of cerebrotendinous xanthomatosis: a rare neuroimaging observation. (14th February 2013) - Jain, Rajendra Singh; Sannegowda, Raghavendra Bakki; Agrawal, Amit; Hemrajani, Deepika; Jain, Rahul; Mathur, Tarun
Abstract : We report a 25-year-old young man presenting with cognitive decline, pancerebellar features, spastic quadriparesis, bilateral cataract (operated) and tendo-Achilles swelling (xanthoma). The CT of the head showed bilateral cerebellar hypodensities. There were bilateral cerebellar hypointensities involving dentate nuclei on T1-weighted images with corresponding hyperintensities on T2-weighted MRI. Additionally, an interesting MRI finding—'hot cross bun' appearance was seen in pons which has not been reported in the literature so far. Biopsy from tendo-Achilles confirmed xanthoma. He was treated with chenodeoxycholic acid following which he showed improvement in cognition and weakness.